Colloidal nanoparticles prepared from zein and casein: interactions, characterizations and emerging food applications - Yi Wang; Wusigale; Yangchao Luo (Food Science and Human Wellness)
Protein colloidal nanoparticles (NPs) are ubiquitous present in nature and function as building blocks with multiple functions in both food formulations and biological processes. Food scientists are inspired by naturally occurring proteins to induce self-assembly behavior of protein by manipulating environmental parameters, providing opportunities to construct special and expected NPs. Zein and casein, the main proteins derived from corn and milk, are two examples of the most prevalently studied food proteins for nanoarchitectures in recent years. In this article, the compositions, structures, and physicochemical properties of these two proteins and casein derivatives are summarized as well as their interactions and characterizations. Strategies to fabricate zein-sodium caseinate based NPs are critically highlighted and illustrated. Particularly, applications such as encapsulation and delivery of bioactive compounds, producing food packaging for enhanced antioxidative and antimicrobial effects, and stabilization of emulsions to achieve fat replacement. Due to the imperative role of food proteins in diet composition, this review not only provides cutting-edge knowledge for nanoparticle construction but also opens new avenues for efficient utilization and exploitation of food proteins.